2016
DOI: 10.1097/01.prs.0000479979.83169.57
|View full text |Cite
|
Sign up to set email alerts
|

Surgeon’s and Caregivers’ Appraisals of Primary Cleft Lip Treatment with and without Nasoalveolar Molding

Abstract: Background Despite the increasing use of nasoalveolar molding (NAM) in early cleft treatment, questions remain about its effectiveness. This study examines clinician and caregiver appraisals of primary cleft lip and nasal reconstruction with and without NAM in a non-randomized, prospective multicenter study. Methods Participants were 110 infants with cleft lip/palate (62 treated with NAM and 48 treated without NAM (NO-NAM)) and their caregivers seeking treatment at one of six high-volume cleft centers. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 26 publications
1
60
0
1
Order By: Relevance
“…An alternative explanation could be that surgery may have a point of diminishing returns. While the timing of surgery and number of procedures may be important to individuals’ OHRQoL, these results suggest that adjunct psychological counseling could provide support to patients and their families undergoing the stress and expectations associated with surgery [36, 37]. …”
Section: Discussionmentioning
confidence: 99%
“…An alternative explanation could be that surgery may have a point of diminishing returns. While the timing of surgery and number of procedures may be important to individuals’ OHRQoL, these results suggest that adjunct psychological counseling could provide support to patients and their families undergoing the stress and expectations associated with surgery [36, 37]. …”
Section: Discussionmentioning
confidence: 99%
“…4,5 NAM has been associated with improved ratings of both predicted and actual surgical outcomes following primary repair. 6,7 NAM has also been associated with decreased rates of secondary revision, 8,9 leading to reductions in total cost of care. 10 However, despite its increasingly widespread use, the efficacy of NAM has thus far been difficult to evaluate.…”
mentioning
confidence: 99%
“…These studies were published between 1998 and 2020 and recruited 684 patients with unilateral cleft lip and palate. Two prospective studies 11 , 12 and 6 retrospective studies were included. 13 18 Two studies did not find differences between the 2 groups (NAM + primary surgery versus primary surgery alone), and 6 studies reported better nasolabial aesthetic outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Broder et al 11 published a nonrandomized prospective multicenter study comparing 2 groups of patients with unilateral cleft lip and palate treated using primary cheilorhinoplasty with and without NAM. Clinicians reported comparable outcomes between the 2 groups, and caregivers reported significantly better outcomes in facial appearance in their patients who underwent NAM.…”
Section: Discussionmentioning
confidence: 99%